Doppler-free spectroscopy of acetylene in near infrared spectral region inside photonic band gap fiber - Thapa, Rajesh (Kansas State University, 2005)
We investigate the nonlinear spectroscopy of acetylene in the near infrared region inside a photonic band gap fiber. The near infrared region of the optical spectrum is an area of intensive research due to its relevance to telecommunication and optical metrology. Acetylene provides a large number of reference transitions coincident with the international telecommunication band. Acetylene contains about 50 strong lines between 1510 nm and 1540 nm in the ν1+ν3 ro-vibrational combination band. We have observed the Doppler-free saturated spectrum of several of these lines. The light from a tunable diode laser at ~1531 nm, resonant with the P(11) transition, is amplified by an erbium doped fiber amplifier and split into a strong pump beam and weak probe beam which counter-propagate inside the gas-filled fiber. The measured Doppler linewidth of the P(11) line at room temperature is about 467 MHz wide. The sub-Doppler profile over a pressure range of 200-1600 mT appears as a narrow absorption feature about 20-40 MHz wide, even at the low pump power of ~10 mW. It is found that for a fiber with an 80 cm length, 20 core size, pumped with 29 mw, the optimum pressure is ~530mT. But the optimum pressure condition will further decrease when the fiber length increases.
Keywords: Saturation spectroscopy in acetylene; Spectroscopy inside photonic band gap fiber; Acetylene; Saturation specroscopy; Spectroscopy in acetylene; Photonic band gap fiber; Fiber cell; Physics, Optics (0752)